Purification of Catalase by Modified Procedure and some Properties of Enzyme - An, Nguyen Hoang; Suminda, Godagama Gamarchchige Dinesh; Phuong, Nguyen Thi Thu; Thai, Dinh Nho; Loan, Nguyen Thi Hong (Academia Journal of Biology, 2018)
Catalase (EC 1.11.1.6) plays an important role in protecting organism from oxidative effect by breaking down H2O2 into H2O and O2 molecules. In this study, a modified procedure for catalase from bovine liver and its properties were reported. Bovine liver catalase was purified to electrophoretic homogeneity as a single protein band around 60 kDa on SDS-PAGE by acetone fractionation, followed by ion-exchange chromatography on DEAE-Sepharose and CM-Sepharose columns. The specific activity of the purified catalase was 79,277 units per mg of protein (U/mg) with 1.87% recovery and purification fold was roughly 60 times. The catalase was a homo-tetramer with a molecular mass of about 240.987 kDa as determined by native gel electrophoresis. The purified enzyme showed the highest activity at pH 7, 37°C, and remained active over a broad range of pH from 5 to 10 and range of temperature from 4°C to 40°C. Its activity was inactivated by incubating in 60°C for 30 min. The activity of the enzyme was induced by Ca2+ and inhibited by Na+, Ni2+, Cu2+, Zn2+, Fe2+, Fe3+ and NaN3. Under the optimal conditions, Km and Kcat/Km values of the catalasewas found to be 23,69 mM and Kcat/Km = 5.106 (M.s)-1, respectively